Image in cardiology - Weich, Hellmuth; Ackermann, Christelle (SA Heart Journal, 2017)
The preferred route for transcatheter aortic valve implantation (TAVI) is via the femoral arteries. These vessels are frequently diseased in the typical elderly TAVI-candidate and therefore require a thorough pre-procedural evaluation. Failure to do so may result in vascular access complications with a high mortality risk. Rodés-Cabau, et al. showed 25% mortality within 30 days in cases with access site complications.(1,2) We therefore advocate imaging of the femoral vessels in all cases with either conventional angiography or CT-angiography.